Twenty-five Years of LIFT: Towards a Plurality of Positions. (February 2020) - Fenton, Rose; Neal, Lucy
Abstract : Rose Fenton and Lucy Neal were the Artistic Directors of LIFT – the London International Festival of Theatre – from its conception in 1979 until their joint resignation in 2004. In this interview they discuss with Phoebe Patey-Ferguson the initial motivations and challenges of establishing an international festival in London and how these changed in maintaining the organization over twenty-five years. This conversation took place in London on 15 February and 14 March 2018, and complements the preceding article in this issue of NTQ by Patey-Ferguson, analyzing the socio-political circumstances of its early years.